Food Insecurity – Overcoming Fragmented Food Systems and Trade Wars - Teng, Paul (2018)
Asia is not likely to produce all the food it needs in the foreseeable future. The fragmented nature of Asian food systems is a major reason. Trade has become an important guarantor of food sufficiency for many ASIAN countries. Taken together, fragmented farming systems and trade wars are threats to Asia’s ability to achieve stable food security.